What are The Clinical and Patient-Reported Outcomes of Different Management Strategies for Recurrent Tonsillitis in Adolescents? : A Comprehensive Systematic Review - Sidqa H; Tiya A (Afiasi : Jurnal Kesehatan Masyarakat, 2024)
Introduction: Recurrent tonsillitis imposes a substantial burden on adolescent health, leading to frequent school absences, reduced quality of life (QoL), and significant healthcare resource utilization. A spectrum of management strategies exists, including tonsillectomy (total or partial), various antibiotic regimens, and watchful waiting. However, a critical evidence gap persists regarding the age-specific efficacy, safety, and impact on patient-reported outcomes (PROs) for adolescents, as most research aggregates data across broader pediatric or adult populations without dedicated subgroup analysis. Methods: A systematic literature search was conducted using PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library. Inclusion criteria targeted studies (meta-analyses, systematic reviews, randomized controlled trials) focusing on recurrent tonsillitis management, with relevant populations (including or overlapping with adolescents aged 10-19), a minimum 6-month follow-up, and reporting of clinical outcomes and/or PROs. From 306 screened sources, data were extracted from the 40 highest-scoring studies. A structured extraction template captured details on management strategies, participant demographics, clinical outcomes (e.g., sore throat frequency, infection rates), PROs (QoL, pain, satisfaction), safety profiles, and comparative effectiveness. Results: Tonsillectomy significantly reduces the frequency of sore throat episodes compared to medical management or watchful waiting, with incidence rate ratios (IRRs) of 0.70 in the first year and 0.54 in the second year post-intervention (Lock et al., 2010). The benefit is maximized with prompt surgery; intervention within 10 weeks of consultation prevented up to 8 sore throats over two years, whereas a 12-month delay reduced this benefit to preventing only 3.5 episodes (Paradise et al., 1984). Tonsillotomy (partial tonsillectomy) demonstrated non-inferiority to total tonsillectomy in controlling infections over a 5-year follow-up but was associated with a significantly lower risk of postoperative haemorrhage (1.6% vs. 5.4%) (Kisser et al., 2024). For medical management, antibiotic prophylaxis with clindamycin and amoxicillin/clavulanate proved superior to penicillin in eradicating Group A Beta-Haemolytic Streptococcus (GABHS) and preventing recurrence, attributable to their stability against beta-lactamase-producing tonsillar flora (Brook, 1989; Asensi et al., 1999). Azithromycin prophylaxis showed comparable long-term (5-year) outcomes to tonsillectomy in moderately affected patients (Diaa El Din El Hennawi & Ahmed, 2016). PROs, measured using validated instruments like the PedsQL and Glasgow Benefit Inventory (GBI), consistently showed improvement following both effective surgical and medical interventions (Kisser et al., 2024; Diaa El Din El Hennawi & Ahmed, 2016). Surgical morbidity, primarily haemorrhage, occurs in 2-7% of cases, with rare mortality (Morad et al., 2017). Discussion: The synthesis indicates that management efficacy is context-dependent. Tonsillectomy is most beneficial for severely affected patients meeting stringent criteria (e.g., Paradise criteria) and when performed expediently. The apparent equivalence between surgery and medical management in some studies can be explained by spontaneous symptom resolution over time in control groups, variable baseline disease severity among study populations, and differences in follow-up duration. For adolescents with contraindications to surgery or moderate disease, medical prophylaxis with beta-lactamase-stable antibiotics or azithromycin is a viable alternative. Surgical technique selection involves trade-offs: tonsillotomy minimizes bleeding risk, intracapsular cobaltion reduces late postoperative pain, and laser/cobaltion techniques improve operative efficiency. A significant limitation is the paucity of studies performing dedicated adolescent subgroup analysis, necessitating extrapolation from broader pediatric data. Conclusion: Tonsillectomy remains a highly effective intervention for severe, recurrent tonsillitis in adolescents, especially when performed without undue delay. Tonsillotomy offers a safer surgical alternative with equivalent long-term infection control. Medical management, particularly with clindamycin, amoxicillin/clavulanate, or azithromycin prophylaxis, represents a valid non-surgical strategy for appropriate candidates. Future research must prioritize prospective studies with age-stratified analyses, longer-term follow-up comparing modern techniques, and standardized assessment of PROs specifically in the adolescent demographic to optimize age-tailored clinical guidelines.